2023
DOI: 10.5755/j02.eie.33866
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Accurate Method for Classifying Tomato Plant Health Status Using Machine Learning and Image Processing

Abstract: Agriculture is crucial to economic growth and development, and maintaining high-quality, disease-free plants is crucial to its success. Early detection of plant diseases, which can be caused by environmental factors, fungi, bacteria, and viruses, is essential to implement appropriate treatments. Tomatoes, which are one of the most vital food crops, are susceptible to diseases that can result in significant economic losses in agriculture. This study introduces a method to evaluate the health of tomato leaf usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…3 There are numerous studies in the areas of plant disease detection and defining plant species. [4][5][6][7] The majority of the time, pre-trained models, proposed models, and private and public datasets are used in these studies. [8][9][10][11] Carrying out disease classification quickly and precisely with the AlexNet architecture was proposed by Singh et al, 12 who used the deep transfer modeling approach to classify the diseases found in the leaves of maize plants.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are numerous studies in the areas of plant disease detection and defining plant species. [4][5][6][7] The majority of the time, pre-trained models, proposed models, and private and public datasets are used in these studies. [8][9][10][11] Carrying out disease classification quickly and precisely with the AlexNet architecture was proposed by Singh et al, 12 who used the deep transfer modeling approach to classify the diseases found in the leaves of maize plants.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of computer equipment constantly enhances the conditions for using more complex measuring algorithms. This is the reason for the increase in the adoption of 3D processing methods in the field of particle assessment [4][5][6]. However, the use of this method is not always the most rational choice.…”
Section: Introductionmentioning
confidence: 99%